Ethnopharmacy of Medicinal Plants in the Production of Ma'jun as Traditional Medicine in Blang Dalam Village, Darul Hikmah District, Aceh Jaya Regency - Vera Maulida; Muhammad Ridhwan; Rubiah; Husna; Cut Morina Zubainur (Jurnal Penelitian Pendidikan IPA, 2026)
Ma'jun is a form of traditional medicinal formulation passed down through generations by the Acehnese community and is commonly used for stamina recovery, treatment of minor ailments, and holistic health therapy. This study aims to explore the types of medicinal plants used in ma'jun production by the community of Blang Dalam Village, Aceh Jaya Regency, and to analyze the ethnobotanical value and pharmacological potential of each species. The research method employed is descriptive ethnobotany with in-depth interviews, participatory observation, and field documentation techniques. The study identified 9 species including other natural materials used in ma'jun formulation, with the dominant plant parts being leaves (60%), roots (20%), seeds (10%), and rhizomes (10%). Literature analysis indicates that most of these species possess pharmacological activities such as anti-inflammatory, antioxidant, immunomodulatory, and gastroprotective properties. These findings confirm that ma'jun is a cultural heritage with great potential to be developed as phytopharmaceuticals based on local wisdom. This study recommends the need for toxicity studies, dose standardization, and further clinical trials.